Angiogenesis protocols - Martin, Stewart; Hewett, Peter (Methods in molecular biology, 2016)
Assessing Tumor Angiogenesis in Histological Samples -- Immunohistochemical Methods for Measuring Tissue Lymphangiogenesis -- Immunohistochemical Assessment of Leukocyte Involvement in Angiogenesis -- Isolation and Culture of Human Endothelial Cells from Micro- And Macro-Vessels -- Isolation, Identification and Culture of Human Lymphatic Endothelial Cells -- Isolation, Culture and Characterisation Of Vascular Smooth Muscle Cells -- Isolation and Transfection of Primary Culture Bovine Retinal Pericytes -- In Vitro Assays for Endothelial Cell Functions Required for Angiogenesis: Proliferation, Motility, Tubular Differentiation And Matrix Proteolysis -- Tube Forming Assays -- In Vitro Co-Culture Assays of Angiogenesis -- Spheroid-Based In Vitro Angiogenesis Model -- Stem Cell Spheroid-Based Sprout Assay in Three-Dimensional Fibrin Scaffold: A Novel In Vitro Model for the Study Of Angiogenesis -- Human Arterial Ring Angiogenesis Assay -- A Modified Aortic Ring Assay to Assess Angiogenic Potential In Vitro -- Quantitative Imaging-Based Examination of Pericyte Control of Endothelial Growth Dynamics and Angiogenesis -- Static and Dynamic Assays of Cell Adhesion Relevant to the Vasculature -- Dorsal Skinfold Chamber Preparation in Mice: Studying Angiogenesis by Intravital Microscopy -- Quantitative Estimation of Tissue Blood Flow Rate -- Chorioallantoic Membrane Microtumor Model to Study the Mechanisms of Tumor Angiogenesis, Vascular Permeability, and Tumor Cell Intravasation -- The Rabbit Corneal Pocket Assay -- The Corneal Micropocket Assay: A Model of Angiogenesis and Lymphangiogenesis -- Models of Oxygen Induced Retinopathy in Rodents -- The Sponge Implant Model of Angiogenesis -- Measurement of Angiogenesis, Arteriolargenesis and Lymphangiogenesis Phenotypes by Use of Two-Dimensional Mesenteric Angiogenesis Assay -- In Vivo Models of Muscle Angiogenes -- Use of the Hollow Fibre Assay to Evaluate Agents that Target The Tumor Neovasculature -- Angiogenesis and Senescence in Zebrafish Embryos. .